Does the Ability to Manage Assets Affect Non-Performing Asset Purchase Decisions? - et. al., Devy M. Puspitasari, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to investigate the relationship between the ability to manage assets to the decision to purchase non-performing assets. The method used in this study uses Partial Least Square (PLS). The unit of analysis used in this research is the executive decision makers in purchasing problem assets during period 2016-2019. The sampling method of this unit of analysis is based on the purposive sampling method. Respondents taken in this study include executives who buy troubled assets in Indonesia with a wide variety of information, which are expected to be more varied and detailed, so that in the end the research results will be obtained as expected. Executives at the level of company owners and top management of the company. The results showed that the decision to purchase non-performing assets is affected by the ability to manage the asset primarily by the post-purchase cost of restructuring the asset and the timing of the asset sale. This study is useful for asset buyers from non-performing loans and non-performing asset management companies. In addition, the network to banks is also an important asset for this business, which relies heavily on a goodwill, which is an intangible asset that banks are specifically familiar with.